TECHNOLOGICAL TESTS USING QUARTZITE RESIDUES AS COMPONENT OF CERAMIC MASS AT THE PORCELAIN STONEWARE PRODUCTION - Souza, Marcondes Mendes (2015)
This work aims to evaluate through technological tests the use of quartzite residues as component at the the production of porcelain stoneware. Were collected five samples of quartzites called of green quartzite, black quartzite, pink quartzite, goldy quartzite, white quartzite. After, the raw materials were milled, passed by a sieve with a Mesh of 200# (Mesh) and characterized by chemical analysis in fluorescence of x-rays and also analysis of the crystalline phases by diffraction of x-rays. The porcelain tiles mass is composed of five formulations containing 57% of feldspar, 37% of clay and 6% of residues of quartzite with different coloration. For the preparation of the specimens, it was used uniaxial pressing, which afterwards were synthesized at 1150°C, 1200°C and 1250°C. After the sintering, the specimens were submit for tests of technological characterization like: water absorption, linear shrinkage, apparently porosity, density and flexural strain at three points. The results presented in the fluorescence of x-rays showed a high-content of iron oxide on black quartzite that is why it was discarded the utilization of it in porcelain stoneware. All quartzite formulations had low water absorption achieved when synthesized at 1200°C, getting 0.1 to 0.36% without having gone through the atomization process. At the tests of flexural strain, all the quartzite had in acceptance limits, according to the European norm EN 100, overcoming 27 MPA at 1200°C